Cosmic-ray neutron fluxes and spectra at different altitudes based on Monte Carlo simulations. (September 2021) - Liu, Huilan; Hou, Yingwei; Li, Hui; Song, Yushou; Hu, Liyuan; Liang, Manchun
Abstract: Cosmic-ray neutrons (CRNs) account for about half of the radiation dose received by airline crews and passengers at aviation altitudes. CRNs also comprise important background radiation near the ground, which should be considered in neutron counts for the purpose of nuclear safeguarding and homeland security. In this study, simulations were conducted with the Geant4 toolkit to describe the air shower of cosmic rays. The latest experimental driving models for the atmosphere, geomagnetic field, and primary galactic cosmic rays were applied in these simulations. The simulation was validated by comparing the results with those measured on the NASA ER-2 aircraft. the CRN fluxes and spectra were calculated at altitudes ranging from one to tens of kilometers. We determined the characteristics of the CRN spectra and analyzed their dependency on the altitude. To consider their impact on the local environment, the CRNs near the ground were modeled with a specific equivalent approach, which allowed the simulations to be conducted with limited computer processing power. The parameters for the incident primary CRNs near the ground were calculated by simulating the cosmic ray air shower. The modeling dimensions were considered for the air and ground, and an appropriate approximation solution was obtained. The model near the ground was used to investigate the dependences of the CRN flux and spectrum on the soil moisture. Highlights: Data-driven atmosphere and geomagnetic field models applied to cosmic-ray air shower. Cosmic-ray neutron flux and spectrum investigated at different altitudes. Cosmic-ray neutron transport near the ground modeled using a specific equivalent approach. Calculated cosmic-ray neutron fluxes and spectra agree well with experimental results.